Implicações gerenciais para o sentido do trabalho - Assis, Adília de (2004)
Work has been the link between individual and organization; both seek and choose each other to do practical, concrete activity. And between individual and his work, we found the manager. Most of personal time is dedicated to work life. If the time passed at work becomes higher, the time that the work must provide significance also highs. And it's not matter of quantitative approach. Work renewal is necessary every day, in qualitative way. It's urgent that work time be more useful, shows purpose and contributes to continuous individual growth and not to his limitation along the time. If the increase of products was the mean challenge of early XX century, today managers face the goal of turning the existent knowledge in the organization useful, productive. The type of product searched today is more intellectual, more valuable, and demands greater employee involvement. We believe that one of the ways of reaching involvement is through the ability of work to provide meaning. Managers can not create meaning for one person, but they actually may intervene in the work organization when it is necessary. This research presents managerial implications from the researched group's point of view: the senses and the absenses of work, and managerial actions in order to administrate this perception. The field research was done along with closed questionaires, with professionals selected from MBA courses. After colecting data, they were treated through statistical parameters based on frequency. The researched group longs for efficiency and results; through clear managerial directions, they seek for their activity's objective. The desire for security at work includes the financial part, but do not exclude the emotional, that therefore was manifested by the wish of doing team work. The quality of manager-subordinate relationship is evident to the meaning of work. There's great demand for managerial habilities of communication (directions, utility of work, feedback). The worry about the invasion of labor at work, with reference to Arendfs concepts, is manifested by the rejection of activities'mechanization and absence of freedom in work execution. The desire of exercising creativity reflects prime need of work intrinsically satisfactory.